Early detection of Autism Spectrum Disorders by primary care physicians: a report on the experience of French-speaking Belgium - Defresne, Pierre; Cappe, Emilie; Willaye, Eric (Belgian Journal of Paediatrics, 2023)
Objective To report on the strategy of early detection of Autism Spectrum Disorder in French-speaking Belgium and to discuss the lessons learned from that experience concerning Autism Spectrum Disorder screening programs, parents’ expectations and well-adjusted health care policies. Methods The program relies on the existing primary health care network, a “two-visits approach” and the association of the M-CHAT-R/F questionnaire with a brief clinical assessment. We analyzed the evolution of the referral of young children between 2016 and 2019 and we interviewed the parents of 101 infants and toddlers detected during the course of the year 2019 about the support which they receive and their unmet expectations. Results Between 2016 and 2019, we noticed a three-fold increase in requests concerning children under 3 years old in our Center. Unfortunately, in the months following early detection of Autism Spectrum Disorder, most French-speaking Belgian families remain without sufficient support and complain of various unmet expectations. Interpretation A strategy of early Autism Spectrum Disorder identification aiming at improving the skills of the primary care practitioners and the network already in charge of the developmental follow-up of children may be a valuable and cost-effective approach. However, along with the improvement of early identification, providing accurate support and effective intervention is crucial for children and families.